(untitled) (London Journal of Medical and Health Research, 2023)
INTRODUCTION: Obstetric Violence is defined as violence committed against women in any period of pregnancy. It can be sexual, physical, psychic and verbal, in addition to negligence, discrimination and/or unnecessary interventionist conduct. OBJETIVE: To characterize the types of Obstetric Violence in Brazil. METHOD: Integrative review of queries in the databases: BVS, PubMed, Medline and Lilacs from January 2017 to September 2022. Descriptors were used individually or combined. N=518 publications were retrieved, after exhaustive reading of the titles and abstracts of the articles, n=460 articles on the subject published in full and available free of charge were selected. After applying the inclusion and exclusion criteria, n=118 studies were selected to be read in full. After these procedures, n=05 papers were selected with a focus on answering the guiding question, on adapting the content used to support the structuring of this integrative review. RESULTS: The analyzed studies are hosted in journals of great scientific relevance prepared by researchers of national and international recognition who guide the decision-making and elaboration of public policies to UN member states. VO presents physical, psychological, sexual, moral and institutional characteristics; Even guaranteed in the Federal Constitution, data point to the lack of a specific regulatory framework to mitigate Obstetric Violence in Brazil. CONCLUSIONS: Obstetric Violence results from gender inequalities: there is gender and age (20 to 34 years), color/race (black, brown and indigenous) social class (poor and lower middle class), schooling (illiterate, semi-illiterate, and with low schooling). It has an address (residents of the regions - north and northeast; inhabitants of ghettos and slums); It presents physical, psychological, sexual, moral and institutional characteristics. It is the role of obstetric nursing to prevent, denounce and promote strategic actions to combat violence, as well as the urgency of the need to create an operational manual for prevention and conduct in the occurrence of OV and the typification of this violence by the legislature. It is important that the Protection, Defense and Support Network works interconnected and articulated with the Extended Clinic.